2018
DOI: 10.1073/pnas.1800039115
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of MycN/CIP2A drives neural crest toward a neural stem cell-like fate: Implications for priming of neuroblastoma

Abstract: Neuroblastoma is a neural crest-derived childhood tumor of the peripheral nervous system in which MycN amplification is a hallmark of poor prognosis. Here we show that is expressed together with phosphorylation-stabilizing factor in regions of the neural plate destined to form the CNS, but MycN is excluded from the neighboring neural crest stem cell domain. Interestingly, ectopic expression of MycN or CIP2A in the neural crest domain biases cells toward CNS-like neural stem cells that express Sox2. Consistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 70 publications
4
42
1
Order By: Relevance
“…This suggests that either SK-N-BE(2)-C cells have retained early transcriptional plasticity, or more intriguingly, that NBs may arise prior to sympathoadrenal differentiation. This notion is supported by developmental experiments showing ectopic MYCN expression in the neural plate border resulting in a shift towards a CNS-like state (Kerosuo et al 2018) and the induction of NB in MYCN-overexpressing NCCs (Olsen et al 2017).…”
Section: Is Wnt Signalling a Major Determinant Of Nc And Nb Cell Fate?mentioning
confidence: 82%
See 1 more Smart Citation
“…This suggests that either SK-N-BE(2)-C cells have retained early transcriptional plasticity, or more intriguingly, that NBs may arise prior to sympathoadrenal differentiation. This notion is supported by developmental experiments showing ectopic MYCN expression in the neural plate border resulting in a shift towards a CNS-like state (Kerosuo et al 2018) and the induction of NB in MYCN-overexpressing NCCs (Olsen et al 2017).…”
Section: Is Wnt Signalling a Major Determinant Of Nc And Nb Cell Fate?mentioning
confidence: 82%
“…This finding was confirmed and extended to show absence of MYCN expression in the condensed dorsal root and sympathetic ganglia. Elevating MYCN expression in the neural plate border was shown to lead to a change in neural crest identity, toward a more central nervous system fate (Kerosuo et al 2018). Transient overexpression of ectopic MYCN in early migrating cells, however, suggested that MYCN can regulate neural crest fate by regulating ventral migration and neuronal differentiation (Wakamatsu et al 1997).…”
Section: Differentiation Of the Neural Crest And Wnt Signallingmentioning
confidence: 99%
“…Moreover, a large number of studies have demonstrated that the MYCN gene is closely related to neuroblastoma . A study by Zaatiti et al indicated that neuroblastoma IMR‐32 cell lines had significantly decreased proliferation ability after MYCN knockout .…”
Section: Discussionmentioning
confidence: 99%
“…Although both MYCN and MYC upregulation occurs in the childhood cancer neuroblastoma, elevated MYCN is the strongest predictor of a poor prognosis [ 54 ]. Given that MYC, not MYCN, is normally expressed in neural crest cells early in chick development, MYCN amplification likely drives aberrant cell specification towards a CNS-like fate to increase tumour aggressiveness, while increased MYC in cells developmentally programmed to express MYC could explain a reduced pathogenicity [ 55 ].…”
Section: Neural Development In Nonmammalian Vertebrates Is Controlmentioning
confidence: 99%